Validation of the revised sport motivation scale (SMS-II) - Pelletier, L. G.; Rocchi, M. A.; Vallerand, R. J.; Deci, E. L.; Ryan, R. M. (Psychology of Sport and Exercise, 2013)
Objectives: Although the Sport Motivation Scale (SMS), published in 1995, has demonstrated validity and reliability in multiple studies, the scale has received some criticisms leading to revisions herein described. The objective of the present studies was to examine the construct validity and reliability of a revised scale sport motivation scale (SMS-II). Design: Two studies were conducted using distinct samples of athletes. Study 1 examined adult athletes participating in a variety of sports and Study 2 examined youth basketball players and swimmers. Method: In Study 1 the SMS-II was introduced and featured various item content changes, a reduced number of items per subscale, the addition of an integrated regulation subscale, and the introduction of a single intrinsic motivation subscale to replace the three intrinsic motivation subscales in the SMS. Relations of SMS-II subscales with each other and with expected outcomes supported the new scale's validity. In Study 2, the structure of the SMS-II and its relations with outcomes were further examined. Results: Results of factor analyses, tests for internal consistency, and correlations among the different subscales and between the subscales and several outcomes of interest, supported the validity of the SMS-II. Conclusions: Discussion focuses on the need for measurement improvement, and potential future directions for SMS-II research.